The Optimization of Biosilica and Humic Acid to Increase Soil Nutrient Availability and Nutrient Uptake in Rice Plant in Sandy Soil - Wanti Mindari; M. Ghufron Chakim; Bakti Wisnu Widjajani; Purnomo Edi Sasongko; Haidar Fari Aditya; Ahmad Mustapha Mohamad Pazi; Seca Gandaseca (Caraka Tani: Journal of Sustainable Agriculture, 2024)
Nutrients in sandy soil are limited due to low absorption capacity and are easily leached or evaporated. Biosilica and humic acid extracted from compost and husk ash can improve the soil structure and absorption capacity to optimize the availability and uptake of nutrients. Therefore, this research aims to examine the optimal application dose of biosilica and humic acid to improve the chemical properties of soil with a sandy texture. The experiment was structured based on a completely randomized design (CRD). Factor 1 consisted of biosilica doses of 0, 0.5, 1.0, and 1.5 tons ha-1, while factor 2 comprised humic acid doses of 0, 20, 40, and 60 kg ha-1. Data analysis was performed using ANOVA, followed by Tukey’s Honest Significant Difference (HSD) test, correlation, and determination analysis. The study results indicate that the combination of biosilica and humic acid contributes to the changes in nutrient availability. The impact of the treatment was observed 90 days after application on the parameters of soil pH, organic C, total N, and exchangeable K. The effects of the treatment were also evident in plant nutrient uptake, specifically in total N in the roots and total K in the stems. The optimal combination for improving soil nutrient availability and nutrient uptake in plant tissues was a biosilica dose of 1.0 tons ha-1 (S2) and humic acid at 40 kg ha-1 (H2).